Evaluasi Kualitas Dan Penggunaan Pdh Polisi Tidak Berseragam Dan Pakaian Dinas Khusus Pegawai Negeri Pada Polri: Evaluasi Kualitas Dan Penggunaan Pdh Polisi Tidak Berseragam Dan Pakaian Dinas Khusus Pegawai Negeri Pada Polri - Harvin Raslin (Jurnal Litbang Polri, 2023)
This evaluation research is hoped that will obtain data, facts and information about the quality and use of uniformed police PDH and civil servant PDK at the National Police so that recommendations for improving the use of PDH and PDK can be given. This research method uses a mixed method, which is a combination of quantitative methods supported by qualitative methods. Qualitative data collection was carried out by means of in-depth interviews with informants consisting of key officials and members of the National Police in 10 (ten) Polda and 34 (thirty four) Polres Rankings as samples. Total respondents in this study were 1953 people.The results of the evaluation showed that the quality of PDH police who were not in uniform had several aspects that were satisfactory, but they still found clothes that felt hot, hot when worn and did not absorb sweat, sizes and seams did not match the members' postures. Supervision is carried out by the PJU Polda and the bearer of the Logistics function. Polres have not been maximally involved in planning, procurement and supervision. The use of PDH police without uniforms has a very positive impact, including increasing a sense of cohesiveness and a sense of kinship, fostering pride, motivation and humanity as well as the professional attitude of members in their duties.